Data scientist under the da. Re perspective: analysis of training offers, skills and challenges - Pires, Flávia (2020)
The digitalization advent is characterized by theincreasing availability of huge amounts of data that allows togenerate new knowledge to support decision-making, problemsolving and process optimization. The successful implementationof this digital transformation strongly depends on the skillsand competences that professionals can have in the differentdimensions of the multidisciplinary vision associated to the datascientist profile. This paper describes a study, conducted underthe scope of the Da.Re Erasmus+ project, that surveys the existingtrainings paths dedicated to the academic education of datascientists and the required hard and soft skills of the job offersfor these professionals. The survey covers three countries of theproject consortium, namely Portugal, Italy and UK